2005
DOI: 10.1007/s10549-005-2420-2
|View full text |Cite
|
Sign up to set email alerts
|

Health-Related Quality of Life in Long Term Breast Cancer Survivors Treated with Breast Conserving Therapy: Impact of Age at Therapy

Abstract: Women of different age treated with BCT for breast cancer should be considered at a different risk for HRQoL disturbance at long term F/U in both, physical and psychological dimensions. In clinical practice, specific identification of those women with negative impact of diagnosis and treatment on long term HRQoL would help for targeted interventions. In clinical studies focusing on HRQoL, the compared groups need to be age-adjusted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
48
2
4

Year Published

2006
2006
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(60 citation statements)
references
References 32 publications
(28 reference statements)
6
48
2
4
Order By: Relevance
“…Longitudinal studies have confirmed fatigue as the most prevalent physical effect after breast cancer treatment 40,44,45 . However, these sa women reported that pain and nerve damage were also largely responsible for a decline in quality of life that limited their ability to function at their previous jobs 46 .…”
Section: Discussionmentioning
confidence: 99%
“…Longitudinal studies have confirmed fatigue as the most prevalent physical effect after breast cancer treatment 40,44,45 . However, these sa women reported that pain and nerve damage were also largely responsible for a decline in quality of life that limited their ability to function at their previous jobs 46 .…”
Section: Discussionmentioning
confidence: 99%
“…This includes clarifying patterns of physical and psychosocial recovery over time, identifying social backgrounds, clinicopathological and treatment-related factors that influence long-term HRQOL, and identifying areas and persons requiring support in the future. Factors with significant effects on long-term HRQOL after treatment of breast cancer include age [18][19][20][21][22][23][24][25], race [9,25], educational status [19][20][21], income [7,8,13], marriage [11,13,21,24,25], recurrence [9,26], disease period [11,20], surgical procedure [7,19,20], chemotherapy [8,10,11,14,20,24], physical activities [27] and culture [25,28]. In our previous longitudinal prospective study, the factors predicting HRQOL at one year after surgery were mood disturbance, poor body image, lower income and positive axillary nodes one month after surgery [17].…”
Section: Introductionmentioning
confidence: 99%
“…As described above, the improvement of overall HRQOL after surgery for breast cancer is generally dependent on the time from diagnosis to treatment, so evaluation at this point is very important when assessing HRQOL [8,22,23]. Social and clinicopathological factors that have significant effects on HRQOL may differ at different time points, and therefore accurate evaluation of HRQOL requires prospective studies.…”
Section: Introductionmentioning
confidence: 99%
“…A influência da idade sobre a reação psicológica ao diagnóstico e ao tratamento antineoplásico remete-nos ao conceito de QV, uma vez que essa reação representa, ao menos parcialmente, o grau de amadurecimento em que a mulher se encontra. Além do impacto psicológi-co, mulheres jovens referem mais dificuldades econômicas 9,10 e maior número de dias perdidos no trabalho 24 . Em recente avaliação de mulheres com média de idade de 43 anos e de tempo de diagnóstico de aproximadamente dois anos, a ausência ao trabalho associou-se negativamente à QV 24 .…”
Section: Idade Ao Diagnósticounclassified
“…Esse quadro pode contribuir para uma percepção negativa da qualidade de vida (QV) 2 . Outros aspectos que podem comprometer a QV de mulheres com câncer de mama relacionamse à diminuição da mobilidade e linfedema do membro superior 6 , uso de quimioterapia 7 , sintomas vasomotores, secura vaginal, disfunções sexuais 8 e dificuldades econômicas 9,10 . A presença de ondas de calor pode comprometer a qualidade e a duração do sono, com conseqüente piora da fadiga 11 e dos sintomas depressivos 4 .…”
unclassified